Green water-based silver nanoplate conductive ink for flexible printed circuit. (2nd January 2016) - Wang, D.-Y.; Chang, Y.; Wang, Y.-X.; Zhang, Q.; Yang, Z.-G.
Abstract : A green water-based silver nanoplate ink was developed for printed circuit board. The growth of the nanoplates was shown by the colour change of the solution. Silver nanoplates with the side length around 20–40 nm in the ink were identified by transmission electron microscope and X-ray diffractomer. The ink patterned on the flexible substrates (polyimide) turned into conductive pattern after sintered at 300°C for 1 hour. The morphology of the conductive patterns were characterised by scanning electron microscopy. After the sintering process, the resistivity of the conductive ink was 9.43μΩ.cm, while the adhesion to the substrate reached 4 B. Thermal gravity analysis was conducted to deduce the mechanism of the sintering process and the solid content of the ink. The application of the conductive ink was also discussed in this paper.